(untitled) (Eurasian Journal of Research, Development and Innovation, 2022)
The article presents the results of the study conflictological competence of teachers of the Russian language in secondary schools. Conflictological competence of the teacher as a condition for positive interaction in the learning environment is an important and relevant topic for the educational organization. freedom of choice of the teacher, subjects, classes and, consequently, the need for compulsory attendance at school is limited; subordination Strict framework of discipline is required. These circumstances require the creation of an environment that reduces the negative factors of the textbook environment and develop skills of constructive interaction. The aim of the study was to identify ways to enhance the conflictological competence of teachers for qualified work with students and their parents in interaction during a conflict educational environment. The paper offers areas of work with teachers that improve conflictological competence